Clean getaway eaudiobook - Stone, Nic (Listening Library, 2020)
From #1 New York Times bestselling author Nic Stone comes a timely middle-grade road-trip story through landmarks of the Civil Rights movement and the map they lay for contemporary race relations. How to Go on an Unplanned Road Trip with Your Grandma: Grab a Suitcase: Prepacked from the big spring break trip that got CANCELLED. Fasten Your Seatbelt: G'ma's never conventional, so this trip won't be either. Use the Green Book: G'ma's most treasured possession. It holds history, memories, and most important, the way home. What Not to Bring: A Cell Phone: Avoid contact with Dad at all costs. Even when G'ma starts acting stranger than usual. Set against the backdrop of the segregation history of the American South, take a trip with this New York Times bestseller and an eleven-year-old boy who is about to discover that the world hasn't always been a welcoming place for kids like him, and things aren't always what they seem—his G'ma included. "Truly a delight." -Christopher Paul Curtis, author of Newbery Medal winner Bud, Not Buddy